THE IMPLEMENTATION OF GUIDED QUESTIONS TECHNIQUE TO TEACH WRITING NARRATIVE TEXT - Erika Marta Sari; Diani Nurhajati; Dewi Kencanawati (LPPM Universitas Kahuripan Kediri, 2026)
Based on a field observations, it was found out that many students found difficulties in organizing their ideas when writing narrative texts. This study aimed to examine the effectiveness of guided questions in teaching narrative writing to eleventh-grade students at SMAN 7 Kediri. A pre-experimental research design was employed involving one class of Grade 11 students. The findings indicated that guided questions significantly assisted students in generating and organizing ideas into well-structured narratives. The students achieved a mean score of 94 in organization, 78.6 in sentence structure, and 74 in mechanics, resulting in an overall writing achievement of approximately 82. In conclusion, guided questions serve as an effective alternative strategy to improve students’ narrative writing skills.